Enhancement of porous asphalt mixtures modified with various fibers and ethylene–vinyl acetate polymer - Kareem G. Nazmey; Mohammed S. Eisa; Ahmed Gamal M. Morsi; Ahmed S. Debaiky (Scientific Reports, 2024)
Abstract Porous asphalt mixture is conventional hot mix asphalt (HMA) with substantially decreased fines, which produces an open-graded mixture that enables the water to flow through an interconnected void space. Porous asphalt is a permeable system that has a lot of benefits. However, because of its open structure, the durability of this mixture decreases, and both its stability and resilient modulus are much lower compared to the dense conventional asphalt mixtures. Also, the high void percentage may lead to an increase in the draindown proportion. Fibers (cellulose or mineral) and polymer-modified binders are recommended for porous asphalt mixtures, especially in hot and moderate climates. The objective of this study is to improve the porous asphalt mixture's performance by using ethylene–vinyl acetate (EVA) polymer-modified bitumen. Two types of fibers (cellulose fibers and glass wool fibers) were used, separately to determine the control mixture. Four different proportions of EVA polymer were added to the bitumen (1%, 2%, 3%, and 4%) and Scanning Electron Microscopy (SEM) was used for better investigating of the bitumen microstructure, then The Marshall mix design was used to determine the optimum EVA content (OEC) for the porous asphalt mixture. Several performance tests were conducted to investigate the characteristics of the porous asphalt mixture, such as the infiltration rate, binder draindown, the wheel track and the cantabro abrasion tests. The findings of the study conclude that the addition of EVA polymer to the porous asphalt mixtures enhances the performance as it increases stability by 20.8% and the infiltration rate by 20.6%. It decreases binder draindown proportion by 33.3%, cantabro abrasion loss by 25.1% and the rut depth at 5,000 cycles and 10,000 cycles by 29.8% and 19.7%, respectively.